Influence of Meteorological Variables on Atmospheric Electric Conductivity over an Urban Location - Kumar, K. C.; Nagaraja, K. (Journal of Scientific Research, 2020)
The measurements of atmospheric electric conductivity along with selected meteorological parameters was carried out at Bengaluru, an urban site in southern India (12.96° N, 77.56° E) during January-December 2015 to understand the electric nature of urban air. During the study period, well defined diurnal variation of conductivity was observed with higher values before sun rise and lower values during afternoon hours. For most of the fair weather days, variations in conductivity show a strong correlation with relative humidity and anti-correlation with ambient temperature. The monthly mean values of conductivity show highest values in winter and lowest in monsoon and interestingly a positive Pearson’s correlation coefficient of +0.5 was found between measured alpha ionization energy and atmospheric conductivity during the study period.